What Do We Learn about Voter Preferences from Conjoint Experiments?. Issue 4 (22nd August 2022) - Abramson, Scott F.; Kocak, Korhan; Magazinnik, Asya
Abstract: Political scientists frequently interpret the results of conjoint experiments as reflective of majority preferences. In this article, we show that the target estimand of conjoint experiments, the average marginal component effect (AMCE), is not well defined in these terms. Even with individually rational experimental subjects, the AMCE can indicate the opposite of the true preference of the majority. To show this, we characterize the preference aggregation rule implied by the AMCE and demonstrate its several undesirable properties. With this result, we provide a method for placing bounds on the proportion of experimental subjects who prefer a given candidate feature. We describe conditions under which the AMCE corresponds in sign with the majority preference. Finally, we offer a structural interpretation of the AMCE and highlight that the problem we describe persists even when a model of voting is imposed.